CONFIGURATION OF CULTURAL NORMS IN TRADITIONAL RICE PLANTING RITUAL DISCOURSE THE TRADITIONAL FARMING COMMUNITY OF BAYAN, NORTH LOMBOK - Netra, I Made; Sutjiati Beratha, Ni Luh; Sutjaja, I Gusti Made; Pastika, I Wayan (e-Journal of Linguistics; Vol. 5. Juli 2011 No. 2, 2011)
This is the study of traditional rice planting ritual discourse of the traditional farming community of Bayan, North Lombok in an ethno-pragmatic perspective.  It is specifically aimed at describing the cultural norms and their meaning configurations.  The theory used in the study is the cultural scripts developed by Wierzbicka (2002a) considering that cultural norms constitute rules and regulations in social interaction practices. They can be investigated from the use of grammatical aspects of language and linguistic routines which are context-bound. They can be configured by paraphrasing in simple and mini language using single space. The results of the study showed that there were some cultural norms found on the traditional rice planting ritual discourse of the traditional farming community of Bayan, North Lombok. They included: (1) asserting thought and hope, (2) respecting other entities, (3) apologizing, (4) promising, and (5) giving advice. The configuration of these cultural norms was in accordance with the understanding of local cultural scripts and wisdom in terms of rituals of the local farming system. The configuration is constructed in low-level script with components of “when” and “if”. It contains the aspects of thinking, speaking, and doing. It is derived from the semantic primes of both evaluation and perception.
Keywords: configuration, cultural norms, ritual discourses, cultural scripts, semantic primes